Breast feeding issue: A study on factors affecting termination of breast feeding among working mothers - Muda, Siti Mariam; Aung, Khin Thandar; Ibrahim, Amirah Fatin; Ismail, Nurul Aini (Galore Knowledge Publication Pvt. Ltd., 2016)
Background: Growth and development of the infants were highly influenced by their first nutrition and breast-milk. Mothers were encouraged to give exclusively breastfeeding as soon as possible after birth up to two years old. However, for working mothers it becomes a challenge for them to continue breastfeeding. Objectives: The aim of this study was to identify the factors that are affecting in termination of breastfeeding among working mothers. And also, the association between socio-demographic data, work related factors and workplace support with breastfeeding practice were examined. Materials and Methods: Self-administered questionnaires were distributed to the government hospital and health clinics in Kuantan, Pahang from March until May 2015. A total of 152 participants were included in this study involving working mothers with children aged six months up to two years old. The factors affecting termination of breastfeeding among working mothers were sociodemographic data, working environment factors and breastfeeding supports were studied. Data was analyzed using the chi-square test in order to determine the relationship between breastfeeding practices with socio-demographic data, work related factors and breastfeeding supports. Results: Most of working mothers in this study stop breastfeeding when they are returning to their work. Strongly supports from the employer at working place significantly affected breastfeeding practices (p<0.05). Conclusion: It is important for the working mothers to have a good support for continuing breastfeeding practice when returning to work from their employers so that they can exclusively breastfeed until the children reached two years old as recommended by the World Health Organization (WHO). Keywords: Breastfeeding Practices, Working mothers, Support.